The Mitochondrial Fission Regulator DRP1 Controls Post-Transcriptional Regulation of TNF-α - Gao, Fushan; Reynolds, Mack B.; Passalacqua, Karla D.; Sexton, Jonathan Z.; Abuaita, Basel H.; O’Riordan, Mary X. D. (Frontiers in Cellular and Infection Microbiology, 2021)
The mitochondrial network plays a critical role in the regulation of innate immune signaling and subsequent production of proinflammatory cytokines such as IFN-β and IL-1β. Dynamin-related protein 1 (DRP1) promotes mitochondrial fission and quality control to maintain cellular homeostasis during infection. However, mechanisms by which DRP1 and mitochondrial dynamics control innate immune signaling and the proinflammatory response are incompletely understood. Here we show that macrophage DRP1 is a positive regulator of TNF-α production during sterile inflammation or bacterial infection. Silencing macrophage DRP1 decreased mitochondrial fragmentation and TNF-α production upon stimulation with lipopolysaccharide (LPS) or methicillin-resistant Staphylococcus aureus (MRSA) infection. The defect in TNF-α induction could not be attributed to changes in gene expression. Instead, DRP1 was required for post-transcriptional control of TNF-α. In contrast, silencing DRP1 enhanced IL-6 and IL-1β production, indicating a distinct mechanism for DRP1-dependent TNF-α regulation. Our results highlight DRP1 as a key player in the macrophage pro-inflammatory response and point to its involvement in post-transcriptional control of TNF-α production.